O Teorema de Bayes: aplicações atuais - Maia, Renato dos Santos (2021)
We live in an increasingly globalized world, where is increasingly common resort to statistical and probabilistic data to take decisions. At the same time, we are experiencing hypotheses that are different from anything we have seen so far, such as the covid-19 pandemic. Thus, in this work, we will do a probabilistic study relating Bayes’ Theorem to the covid, through Bayesian inference, and thus, we can give a more intriguing and current touch that can be used to attract more people to mathematics.